RESEARCH ON STIFFNESS REDUCTION OF UNIDIRECTIONAL LAMINATES UNDER STATIC TENSILE LOADS - WANG Le; WU FuQiang (Jixie qiangdu)
The stiffness of unidirectional laminates will reduce due to damage under static tensile loads. By analyzing the failure process of unidirectional laminates,study on the effect of stiffness reduction caused by the longitudinal,transverse and shear stress components was conducted. A new model of stiffness progressive reduction considering loads and ply angles was established. The rationality of this model was verified by static tensile tests of series of T700/YPX3001 unidirectional laminates with different ply angles. A numerical simulation based on the proposed model of the failure process of unidirectional laminates under static tensile loads was implemented. The analysis results are in good agreement with experimental results.